2021
DOI: 10.1177/1070496521995872
|View full text |Cite
|
Sign up to set email alerts
|

China’s Blue Economy: A State Project of Modernisation

Abstract: The blue economy is a globally emerging concept for ocean governance that seeks to tap the economic potential of the oceans in environmentally sustainable ways. Yet, understanding and implementation of particular visions of the blue economy in specific regions diverge according to national and other contexts. Drawing on a discourse analysis of Chinese language documents, this article assesses how the blue economy has been conceptualised in Chinese state policy and discourse. Part of a state ideology and practi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 70 publications
0
10
0
Order By: Relevance
“…This expansion is part of a national development plan designed to reduce pressure on coastal fisheries, provide work for shipyards, supply raw materials to domestic fish factories, and expand diplomatic influence. 81 Although Korea, Japan, Taiwan, and China remain the dominant DW fishing nations, the number of vessels flagged to other states has increased as a number of operators have begun relying on open registries and/or flags of convenience to avoid those regulations whose enforcement is contingent on the engagement and goodwill of national authorities. 82,83 Confronted with declining economic returns, many DW fishing fleets across the Pacific have adopted new technologies and operational strategies to remain profitable.…”
Section: Demographic and Operational Change In Longline Fisheriesmentioning
confidence: 99%
“…This expansion is part of a national development plan designed to reduce pressure on coastal fisheries, provide work for shipyards, supply raw materials to domestic fish factories, and expand diplomatic influence. 81 Although Korea, Japan, Taiwan, and China remain the dominant DW fishing nations, the number of vessels flagged to other states has increased as a number of operators have begun relying on open registries and/or flags of convenience to avoid those regulations whose enforcement is contingent on the engagement and goodwill of national authorities. 82,83 Confronted with declining economic returns, many DW fishing fleets across the Pacific have adopted new technologies and operational strategies to remain profitable.…”
Section: Demographic and Operational Change In Longline Fisheriesmentioning
confidence: 99%
“…One of the significant challenges associated with the concept of the Blue Economy is the range of different ways in which the term (and associated terms such as Blue Growth and sustainable ocean economy) are employed in different, and often competing ways. For example, Fabinyi et al [4] found that China is employing the Blue Economy as a form of state led modernization and economic growth, while an analysis by Satizábal et al [5] found that the Filipino Blue Economy agenda has focused heavily on payment for ecosystems services and natural capital accounting, with particular emphasis on Blue Carbon initiatives. These inconsistencies have been highlighted to be both a challenge and an opportunity for actors wishing to engage with the Blue Economy, as these differences create the potential for both conflict and flexibility [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Fabinyi et al . [4] found that China is employing the Blue Economy as a form of state led modernization and economic growth, while an analysis by Satizábal et al . [5] found that the Filipino Blue Economy agenda has focused heavily on payment for ecosystems services and natural capital accounting, with particular emphasis on Blue Carbon initiatives.…”
Section: Introductionmentioning
confidence: 99%
“…By tracing the various constructions of blue economy promises within mainstream global discourses, this paper contends that patterns can be observed in the agenda's 10-year career which, when read together, detail a narrative of retreating equity and a deepening preoccupation with economic growth. Critically, this paper understands the blue economy as a socially embedded agenda that can only be adequately analyzed and understood in the context of its various socio-historical settings (Garland et al, 2019;Bogadóttir, 2020;Fabinyi et al, 2021;Louey, 2022). This encourages an analysis of the broader socio-political ecosystems within which the blue economy and various promises have been articulated, ultimately situating it in the longer histories of sustainable development, modern geopolitics and neoliberalism.…”
Section: Introductionmentioning
confidence: 99%